Effect of Racephenicol on Antibiotic Resistance of Lactose-Fermenting Enteric Bacteria in Chickens - Rollins, Larry D. (1973)
The incidence of lactose-fermenting enteric organisms resistant to chloramphenicol increased from less than 0.1% prior to treatment to more than 90% in two groups of chickens fed racephenicol-supplemented feed at 50 or 140 g/ton for 10 days, whereas controls remained unchanged. A concurrent increase in the incidence of organisms resistant to dihydrostreptomycin, oxytetracycline, ampicillin, and sulfonamides also occurred. Minimum inhibitory concentrations for chloramphenicol increased from <10 μg/ml to >300 μg/ml in most Escherichia coli isolates in response to treatment. The observed resistance was transferable to E. coli and Salmonella.